Environmental Impact of Oil and Gas Exploration on Livelihoods in Nigeria's Eastern Obolo: Exploring the People's Rights to Fair Compensation. Issue 3 (2nd September 2021) - Adonteng-Kissi, Obed; Oke, Benson R.; Meribe, Nnaemeka Chidiebere; Ayentimi, Desmond Tutu
Abstract: This paper explores how adequate are oil and gas companies to compensate the damage done by their oil exploration. The study is based extensively on primary fieldwork in local host communities in the oil-producing areas of Eastern Obolo in Rivers State, Nigeria drawing on the experiences and perceptions of 31 community heads, Chief fishermen, youth leaders, the chairman of the Eastern Obolo Community Relations Committee (CRC), the paramount chief and sub-chiefs, and Community Relations Managers of Oil Companies. The average age of participants was 37 years. Semi-structured interviews were conducted with key informants using in-depth interview techniques to gather the needed data. Our results show that distributive and procedural justice and people's rights to self-determination and fair compensation have been compromised in policy initiatives. Harmonising layers of critical laws, including the enforcement of social and environmental protection, must remain a priority though challenges inherent in the legal framework regulating compensation go beyond the impacts of social and environmental governance.